Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T17:54:44+01:00
-2x+1=4
-2x=3 / :(-2)
x=-3/2

2x+2=x
x=-2

2t-3t-1=6
-t=7 / *(-1)
t=-7

-4-x=6-2x
2x-x=6+4
x=10

3y+18-y=2y+18
3y-y-2y=18-18
0=0



2010-03-11T18:03:57+01:00
-(2x-1)=4
-2x+1=4 |-1
-2x = 3 |: (-2)
x=-1,5


2(x+1)=x
2x+2 =x |-2
2x=x-2 |-x
x=-2

2t-(3t+1)=6
2t-3t-1=6
-t-1=6 |+1
-t=7 |*(-1)
t=-7


-(4+x)=2(3-x)
-4-x=6-2x |+4
-x=10-2x |+2x
x=10

3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
0=0
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3 |+17
-5x=20 |:(-5)
x=-4